PENGARUH KEPUASAN KERJA DAN KOMITMEN ORGANISASI TERHADAP TURNOVER INTENTION KARYAWAN (Studi pada PT. Bank Perkreditan Rakyat Mitratama Arthabuana) - Abdurrahim; Hastin Umi Anisah (JWM (JURNAL WAWASAN MANAJEMEN), 2015)
This study aimed to identify and analyze the influence of job satisfaction (X1) and organizational commitment (X2) as independent variables either simultaneously or individually on Turnover Intention (Y) as the dependent variable on the employee of PT. BPR Mitratama Arthabuana Kertak Hanyar. This was an explanatory research with unit analysis of PT. BPR Mitratama Arthabuana Kertak Hanyar. The sampling technique used in this study was saturated sample with 53 employees as population. Measurement of variables is done by using Likert Scale technique with weight scale from 1 to 5. Multiple linear regression statistical technique were used to analyze the effect of job satisfaction among variables (X1) and organizational commitment (X2) on Turnover Intention (Y). Furthermore, to test the level of significance, the F test and t test with SPSS version 19 used. The study concluded that two independent variables simultaneously, namely job satisfaction variables (X1) and organizational commitment (X2) have significant relationship to Turnover Intention (Y) variable. Meanwhile, individually, job satisfaction variable (X1) has significant negative relationship on Turnover Intention (Y), as well as the organizational commitment variable (X2) on a Turnover Intention (Y